Leiden mutation (rs6025) in a severe COVID-19 pneumonia patient with Down syndrome: a clinical case - Pokhylko , V.I.; Cherniavska , Y.I.; Fishchuk , L.Y.; Rossokha , Z.I.; Ievseienkova , O.G.; Dubitska , O.M.; Popova , O.F.; Fastovets M.М.; Kaliuzhka O.О.; Gorovenko , N.G. (Medicni Perspektivi, 2023)
COVID-19 was first reported in December 2019 in Wuhan (Hubei Province, China). Later, the pandemic of this disease took the world by storm, challenging the medical community. Its clinical manifestations vary from asymptomatic to a severe course that requires hospitalization and intensive therapy with oxygen support. The mortality rate in patients with a severe course of COVID-19 can exceed 50% The majority of fatal cases of COVID-19 were associated with thrombotic events, despite the prophylactic use of anticoagulant therapy. Numerous theoretical overviews and research articles indicate the need for genetic testing in patients with COVID-19 to determine the genetic profile of proteins involved in thrombophilia. According to the researchers, the Leiden mutation (G1691A, rs6025) of the FV gene is one of the promising candidates for testing. The aim of the work was to demonstrate the clinical features of the severe course of COVID-19 in the presence of the Leiden mutation. 58 patients with COVID-19 of the intensive care unit were genotyped. The Leiden mutation in the heterozygous state was found only in one patient, who had Down syndrome. The Leiden mutation was detected with a frequency of 1.72% in the investigated group. The described clinical case clearly showed that individuals with Down syndrome, associated with hereditary thrombophilia are at risk of undesirable clinical consequences in the treatment of COVID-19. The condition of the patient with the Leiden mutation was severe when admitted to the hospital. The score according to the sequential organ failure assessment scale was 2 points. Bilateral multisegmental pneumonia was detected on the X-ray. On the second day after admission, due to the development of acute respiratory distress syndrome and multiple organ failure, the patient was transferred to the intensive care unit, where he received oxygen therapy through a facial mask. Medical treatment was carried out according to the protocol: non-steroidal anti-inflammatory drugs, antibacterial therapy, anticoagulants, sympatho¬mimetics, and glucocorticosteroids. Despite the medical measures taken, progression of respiratory failure, renal failure, and portal hypertension was noted. On the 11th day, the patient developed asystole. Resuscitation measures were unsuccessful. Thus, the described case of a severe course of COVID-19 in a carrier of a heterozygous variant of the Leiden mutation with Down syndrome confirms the recommendations regarding the need for genetic testing for thrombophilia in high-risk groups and the appointment of personalized measures to prevent complications.